Hubungan Tingkat Pendidikan dengan Tingkat Ketertarikan Masyarakat terhadap Pelayanan Gizi berbasis Gen di Indonesia: Hubungan Tingkat Pendidikan dengan Tingkat Ketertarikan Masyarakat terhadap Pelayanan Gizi berbasis Gen di Indonesia - Listiyana, Fani; Aji, Arif Sabta; Sari, Sintha Dewi Purnama; Irwanti, Winda; Wulandari, Fatma Annisa; Khouridhiya, Mumtaz; Surendran, Shelini (Amerta Nutrition, 2023)
Background: Non-communicable diseases (NCDs) constitute significant causes of global mortality, with their prevalence continually rising each year. The development of nutrigenetic science and gene-based nutrition services plays a vital role in mitigating NCDs, despite the lack of awareness among many individuals.  Objectives: This study aims to investigate the relationship between education levels and the level of interest in gene-based nutrition services among Indonesians.  Methods: A cross-sectional study design was conducted online using the Qualtrics Survey during May and June 2023 in DKI Jakarta, West Java, Central Java, East Java, and DI Yogyakarta. The cluster sampling technique was employed. Structured questionnaires were designed, covering sociodemographic information and interest levels, and were validated and tested for reliability. Data analysis involved chi-square testing.  Results: Indonesians exhibited a substantial interest in gene-based nutrition services (92.3%). Most participants (89.7%) expressed willingness to recommend nutrigenetic testing to their families. Additionally, 97.5% of participants agreed that gene-based nutrition services offer numerous benefits (97.5%), and a significant proportion was open to paying more for such services (62.4%). A large percentage of Indonesians demonstrated interest in undergoing nutrigenetic testing to ascertain disease susceptibility (95.9%). However, no significant association was observed between education levels and the interest in gene-based nutrition services in Indonesia (p=0.134, OR: 0.551, CI=95% (0.27-1.11)).  Conclusions: The study findings suggest that the educational background of Indonesians does not significantly impact their interest in gene-based nutrition services. However, a majority of Indonesians display interest and recognize the potential benefits of gene-based nutrition services, particularly in the context of preventing NCDs.